The effects of motor learning after unilateral stroke: A Systematic Review - Ailin Talimkhani; Iraj Abdollahi; Behnam Akhbari; Fatemeh Ehsani; Omolbanin Abaspour (Vesnu Publications, 2015)
Introduction: The purpose of the present study is to review the previously published studies concerning effective of motor learning after unilateral stroke. Materials and Methods: A literature search for the period of 1995-2013 was performed using ProQuest , ,Elsevier and science direct, google scholar, PubMed databases. Cerebral vascular accident , hemiplegia, stroke ,learning, motor learning, recovery, functional recovery were used as keywords. Results: Ten articles were selected according to the inclusion criteria of the study. There was a wide variation among studies in terms of methodology, severity of stroke, locus of brain damage, sample size, procedure. Conclusion: The results demonstrated that there is adequate evidence to support that motor learning capability of individuals with unilateral stroke has preserved when type of  task and feedback, explicit information do not increase demand of working memory or severity of stroke be mild Key words: unilateral stroke, motor learning, functional recovery